Monogram on Soil and Water Conservation in Uttar Pradesh during the V Five-year Plan - Sahai, Rameshwar (Indian Forester, 1973)
Uttar Pradesh is one of the 5 major States of India. It ranks I in population and IV in area. It has, among the big States, the largest variation in altitude and topography. 18 per cent of its total area is subject to soil erosion, of which 10 per cent lies in the Gangetic plain and 8 per cent in the Himalayan and semi-hilly regions. Soil erosion in undulating areas affects the fertility of agricultural lands; reduces the life of reservoirs, due to silting up of beds. Soil erosion in the Himalayan region during rains causes silting up of river beds in the plains, resulting in annual floods. The problem of soil erosion is man-made. It does not exist in virgin areas, untouched by man, as such areas have a natural protection of green vegetation. What is really required is to stop growing agricultural crops in those undulating areas which are considered unfit for agriculture, and utilise it for alforestation. Conservation of water resources and control of floods are closely linked with soil conservation. In virgin land floods seldom occur. Man uses flood plain for agriculture, and this is responsible for floods along banks of streams. The principal methods of protection against floods are enumerated. The criteria for selecting a river for training against floods are also given. The rules to be followed for Soil and Water Conservation during the V Five-Year Plan are enumerated. Each type of land should be allotted to that form of use under which it would produce most and deteriorate least. For the Himalyan region, horticulture shoulh gradually replace agriculture wherever possible. This would greatly reduce soil erosion in the Himalayan region during the rains which is responsible for silting up of river beds in the plains, and consequent destructive annual floods.